THE PROBLEM OF TRANSLATING REALIA - Makhsudaliyeva, M.; Kosimova, M. (Educational Research in Universal Sciences, 2023)
This article demonstrates brief description of the concept of ‘Realia’ and discusses several problems that can be come across during translating them. Realia indicates specific cultural elements and expressions. Translating realia has been studied for so many years. However, there is some confusion in giving correct translation because of different cultural features. Here are given several solutions and tips that prevent wrong translation.